THE ROLE OF COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF ISCHEMIC STROKE - Bakhritdinov B.R. (Journal of new century innovations, 2023)
Annotation. The analysis of literature data and cooperative disorders for the evaluation of ischemic strokes was carried out. MSCT is a highly informative non- invasive method in the diagnosis of strokes, especially at the acute stage. Various MSCT protocols were used, which accurately assess the prevalence and dynamics of ischemic changes in the assessment of differential diagnosis, as well as to assess the severity of edema.